Effect of smoking on the survival of dental implants - Takamiya, Aline Satie [UNESP]; Goiato, Marcelo Coelho [UNESP]; Gennari Filho, Humberto [UNESP] (Palacky University Olomouc, 2014)
Background. Although the long-term success of implant treatment has been well- established, failures can still occur and the smoking habit has been reported as a risk factor for implant loss. A literature review on the effects of smoking on the survival of dental implants was undertaken. Methods and Results. Medline database was used to carry out the review with the keywords “osseointegration”, “smoking” and “bone healing”. The cigarette has more than 4,000 bioactive chemical components with potential toxic effects to human tissues including bone. Nicotine is the main component of the cigarette and it is frequently associated with bone healing failures. Since smoking negatively affects the osseointegration of dental implants, the main target is to quit the consumption of cigarettes. Conclusion. Nevertheless, the smoking habit should not be an absolute contraindication for implant treatment, but, patients should be advised that they are at a greater risk of implant failure.
Keywords: Smoking; Bone healing; Osseointegration; Dental implants